PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJAPEGAWAI PADA DINAS PERTANIAN KABUPATEN SUPIORI - Johanes Eliezer Ayer; Lyndon R.J. Pangemanan; Yolanda P. I. Rori (Sam Ratulangi University, 2016)
This study aims to identify and analyze whether there is influence of motivation and discipline ito the performance of employees in the Agriculture Office of Supiori District, Papua Province. This research is classified as causal research associative quantitative approach to the instrument in the form of a questionnaire. The population in this study were all employees of the District Agriculture Office Supiori as many as 80 people. The sampling technique by means of saturated or census sampling technique. The sample in this research is to take the population, or as many as 80 samples. The data used in this study are primary data obtained through questionnaires and secondary data related agencies and journals to support this research. Test the validity of the instrument using bivariate Correclation formula, while the reliability test using Cronbach Alpha. Measuring instrument proved valid and reliable for research instruments. Multiple regression analysis used to test hypotheses of this study. The results showed that: motivation (X1) positive and significant impact on employee performance of Agriculture Office in Supiori District (ï¢) 0.413 with significantly 0,01. Labor discipline (X2) positive and significant impact on employee performance Supiori of Agriculture Office (ï¢) 0.741 with significantly by 0,00. And based on the test results both independent variables were tested individually dominant in influencing the performance of employees in Supiori District Agriculture Office is working discipline (with a coefficient of 0.489). It can be concluded that in this study the discipline of work (X2) partially are factors that significantly affect performance (Y).